Climate Change: A Very Short Introduction - Maslin, Mark (New York Oxford University Press, 2014)
In the new edition of 'Climate Change', Mark Maslin explores all of the key debates. Examining the most recent scientific research, he looks what climate change is, its impact on our planet, and why it's such a complex problem to solve.
Includes Index and Illustrations.
Keywords: Climatic changes